Gasless single incision trans-axillary thyroidectomy: The feasibility and safety of a hypo-morbid endoscopic thyroidectomy technique - Panchangam R K Bhargav; Uday S Kumbhar; G Satyam; K B Gayathri (Journal of Minimal Access Surgery, 2013)
Introduction: A range of minimally invasive endoscopic techniques (gas dependent and gasless) have been attempted for thyroidectomy in the past two decades. In this context, we evaluated the feasibility and safety of our technique of a gasless trans-axillary thyroidectomy. Material and Methods: This retrospective study from the Department of Endocrine and metabolic surgery in Southern India included 15 cases. The details of operative technique, intra and postoperative data were documented in all the cases. Only cases with benign thyroid nodules were included. Exclusion criteria were diffuse toxic goiters (Graves′ disease), thyroid cancer, > 6 cm nodules, recurrent goitres and patients with shoulder joint pathology. Statistical analysis was done with SPSS software 12.0 version. Results: F:M -14:2. Mean age of the patient group was 26.4 years (15-52). Mean operative time was 123.4 (82-206) minutes. The only specific complications were induration in the infraclavicular area between axillary incision and thyroid region, prolonged wound drainage and stiffness in lower 3 rd of sternocleidomastoid. Wound drainage lasted for 5.4 days (4 -8). There was no significant operative morbidity. Conclusion: This gasless trans-axillary technique for nodular goitres is safe and effective in the hands of an experienced thyroid surgeon.